2020
DOI: 10.1128/mbio.00939-20
|View full text |Cite
|
Sign up to set email alerts
|

An Essential Membrane Protein Modulates the Proteolysis of LpxC to Control Lipopolysaccharide Synthesis in Escherichia coli

Abstract: Gram-negative bacteria are surrounded by a complex cell envelope that includes two membranes. The outer membrane prevents many drugs from entering these cells and is thus a major determinant of their intrinsic antibiotic resistance. This barrier function is imparted by the asymmetric architecture of the membrane with lipopolysaccharide (LPS) in the outer leaflet and phospholipids in the inner leaflet. The LPS and phospholipid synthesis pathways share an intermediate. Proper membrane biogenesis therefore requir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(63 citation statements)
references
References 44 publications
3
60
0
Order By: Relevance
“…Another variant of LpxC R230C as the suppressor of lapC mutants was also isolated three times that also resulted in elevated levels of LpxC. During the completion of this work, two independent studies also reported the isolation of suppressors of lapC that caused alterations of either V37 or R230 amino acids, respectively [35,36]. It is of interest that we isolated additional variants of LpxC that suppress lapC190 and lapC377fs mutations, which were not reported in other complementary studies mentioned above, providing a broader model of LpxC regulation and help in understanding the function of LapC.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Another variant of LpxC R230C as the suppressor of lapC mutants was also isolated three times that also resulted in elevated levels of LpxC. During the completion of this work, two independent studies also reported the isolation of suppressors of lapC that caused alterations of either V37 or R230 amino acids, respectively [35,36]. It is of interest that we isolated additional variants of LpxC that suppress lapC190 and lapC377fs mutations, which were not reported in other complementary studies mentioned above, providing a broader model of LpxC regulation and help in understanding the function of LapC.…”
Section: Discussionmentioning
confidence: 89%
“…Thus, in the first approach, Tn10-linked point mutations that simultaneously exhibited the elevated rpoEP3 promoter activity, the sensitivity to the LpxC inhibitor CHIR090 to different extents and membrane permeability defects were analyzed leading to the identification of three point mutations: one having a frame-shift mutation resulting in truncation after 377 amino acid residue isolated three times, the second mutation introduces a stop codon after amino acid residue 190, another resulting into a single amino acid F349S substitution, in the essential yejM gene. During the completion of this work, YejM has been speculated to either maintain lipid homeostasis or be involved in the transport of cardiolipin or exhibit a metal-dependent phosphatase activity [31][32][33][34][35][36][37]. We designated this gene lapC based on identified genetic and biochemical interactions of LapC with LapB.…”
Section: Introductionmentioning
confidence: 99%
“…Three consecutive papers from the Silhavy ( 10 ), Bernhardt ( 12 ), and Misra ( 13 ) laboratories revealed the essential role of YejM in E. coli through suppressor analysis. The Misra group began by generating suppressors to large antibiotics (erythromycin and vancomycin) in a hypersensitive E. coli mutant that produces a periplasmic-truncated YejM ( 13 ).…”
Section: Emerging Role In Lps Regulationmentioning
confidence: 99%
“…Furthermore, Bernhardt and colleagues isolated viable suppressors in E. coli lacking the complete YejM protein, and these suppressors were mapped to lpxC and lapB ( 12 ). Like the Misra laboratory, they also revealed that stabilizing LpxC levels rescued yejM mutants ( 12 ).…”
Section: Emerging Role In Lps Regulationmentioning
confidence: 99%
“…1A). Recent papers, one of which is in this issue of the journal (3), find a regulatory role for one of the last essential genes (yejM) in Escherichia coli that lacks a clear function (4,5). The papers provide evidence that YejM senses an intermediate in these biosynthetic pathways to regulate the stability of LpxC, a key enzyme in the biosynthesis of LPS (6,7), to balance the synthesis of PL with LPS and maintain OM asymmetry.…”
mentioning
confidence: 99%